Springer Handbook of Acoustics - e; SpringerLink (Online service) (New York, NY : Springer New York, 2007)
Acoustics, the science of sound, has developed into a broad interdisciplinary field encompassing the academic disciplines of physics, engineering, psychology, speech, audiology, music, architecture, physiology, neuroscience, and others. The Springer Handbook of Acoustics is an unparalleled modern handbook reflecting this richly interdisciplinary nature edited by one of the acknowledged masters in the field, Thomas Rossing. Researchers and students benefit from the comprehensive contents spanning: animal acoustics including infrasound and ultrasound, environmental noise control, music and human speech and singing, physiological and psychological acoustics, architectural acoustics, physical and engineering acoustics, signal processing, medical acoustics, and ocean acoustics. This handbook reviews the most important areas of acoustics, with emphasis on current research. The authors of the various chapters are all experts in their fields. Each chapter is richly illustrated with figures and tables. The latest research and applications are incorporated throughout, e.g. computer recognition and synthesis of speech, physiological acoustics, psychological acoustics, thermoacoustics, diagnostic imaging and therapeutic applications and acoustical oceanography. With a Foreword by Manfred R. Schroeder Key Topics Physical and Engineering Acoustics Signal Processing in Acoustics Physiological and Psychological Acoustics Architectural Acoustics Medical Acoustics Ocean Acoustics Environmental Noise Control Musical Acoustics, Human Speech and Singing Animal Acoustics (Infrasound and Ultrasound) Features Contains over 960 two-color illustrations. Includes over 80 comprehensive tables. Emphasizes physical concepts over extensive mathematical derivations. Delivers a wealth of up-to-date references. Parts and chapters with summaries, detailed index and fully searchable CD-ROM guarantee quick access to data and links to other sources. Audio and video files on CD-ROM.
Foreword by Manfred R. Schroeder -- Introduction to acoustics -- History of acoustics -- General linear acoustics -- Sound propagation in the atmosphere -- Underwater acoustics -- Physical acoustics -- Thermoacoustics -- Nonlinear acoustics -- Performance and assembly hall acoustics -- Concert hall acoustics - Subjective preference theory -- Building acoustics -- Physiological acoustics -- Psychoacoustics -- Acoustic signal processing -- Musical acoustics -- Speech and singing -- Computer music -- Audio and electroacoustics -- Animal bioacoustics -- Cetacean acoustics -- Medical ultrasound -- Structural acoustics and vibration -- Noise -- Microphones and their calibration -- Sound intensity -- Acoustic holography -- Optical methods for acoustics and vibration -- Modal analysis -- About the Authors -- Subject Index.
Keywords: Physics; Animal physiology; Acoustics; Optics; Electrodynamics; Engineering; Physics; Acoustics; Animal Physiology; Optics and Electrodynamics; Engineering, general; Signal, Image and Speech Processing; Electronic books